Surface treatment process of through-hole thin film ceramic substrate

By drilling, grinding and cleaning, annealing, ultrasonic cleaning, magnetron sputtering and electroplating copper thickening, the problem of large pore diameter and large slag after laser punching of ceramic substrates is solved, and the substrate is improved Reliability and yield.

CN118248562BActive Publication Date: 2025-02-11江苏富乐华功率半导体研究院有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410373316.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2025-02-11
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

After laser punching of ceramic substrates, the aperture taper is large and the orifice is slag is large, resulting in poor bonding performance between metal and ceramics, affecting the reliability and yield of the substrate.

Method used

Using a surface treatment process of through-hole thin film ceramic substrate, including drilling, grinding and cleaning, annealing, ultrasonic cleaning, magnetron sputtering and electroplating copper thickening, remove slag in the orifices and holes, and improve metal and Ceramic bonding properties.

Benefits of technology

Through this process, the reliability and yield of the ceramic substrate are significantly improved, and the poor bonding problem caused by raw materials and process reasons are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118248562B_ABST
    Figure CN118248562B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of semiconductor technology, and specifically to a surface treatment process for a through-hole thin-film ceramic substrate. The present invention prepares a finished product by sequentially performing ceramic laser punching patterns, grinding treatment + annealing + ultrasonic cleaning treatment, magnetron sputtering metal layers, and electroplating thickening on a ceramic substrate. The present invention uses a surface treatment process for a through-hole thin-film ceramic substrate to effectively reduce the problems of hole burrs, hole wall ceramic slag, and surface slag caused by laser punching, thereby reducing the abnormal metallization bonding force of the substrate and improving the yield rate of the through-hole thin-film ceramic substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductors, in particular to a surface treatment process for a through-hole thin-film ceramic substrate. Background Art

[0002] With the rapid development of the microelectronics packaging industry, electronic packaging technology is developing in the direction of miniaturization, high density, multi-power and high reliability. As an industrial field with high technology content and high economic benefits, electronic packaging materials play an important role. Ultra-thin composite substrate is a material made of advanced ceramic materials with excellent electrical insulation properties, high thermal conductivity, excellent brazing properties and high bonding strength. In addition, it can also etch various patterns like PCB boards and has a large current carrying capacity. Due to these advantages, ceramic substrates have become the basic materials for high-power power electronic circuit structure technology and interconnection technology. When designing thin-film circuit substrates, through holes are necessary to achieve three-dimensional packaging, reduce device volume and increase packaging integration. Therefore, through-hole filling substrates have been widely used in structured packaging. However, due to the characteristics of ceramic materials themselves, conventional physical drilling methods are not suitable for ceramic substrates, and can only be punched or punched by laser equipment. Although laser punching has the advantages of high efficiency, speed and high precision, its defects are large aperture taper and more orifice slag. To address this problem, a surface treatment process for through-hole thin-film ceramic substrates is proposed, which can effectively remove the slag at the hole mouth and inside the hole and improve the bonding performance between metal and ceramic. This process can further improve the reliability and yield of the substrate.

[0003] In order to overcome the defects of the prior art, the present invention provides a surface treatment process for a through-hole thin film ceramic substrate. Summary of the invention

[0004] The object of the present invention is to provide a surface treatment process for a through-hole thin-film ceramic substrate to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A surface treatment process for a through-hole thin-film ceramic substrate comprises the following steps:

[0007] Step 1: Punch holes in the ceramic substrate;

[0008] Step 2: grinding and cleaning the surface of the ceramic substrate obtained in step 1, annealing, ultrasonic cleaning, and baking at 100-120° C. for 60 min-120 min;

[0009] Step 3: magnetron sputtering is performed on the surface of the ceramic substrate obtained in step 2 to sputter a titanium transition layer and a copper metal layer respectively;

[0010] Step 4: The ceramic substrate obtained in step 3 is thickened by electroplating copper to obtain a finished product.

[0011] More optimally, in step one, the ceramic substrate is punched by laser punching. The ceramic substrate is laser punched using fiber laser ceramic processing equipment. The ceramic substrate is placed on a vacuum adsorption platform, and a specified pattern and aperture are set. The aperture is 70-100 μm, the instantaneous power is 1500-1800 W, and the average power is 500-700 W.

[0012] More optimally, in step one, the ceramic substrate is one or more of an aluminum oxide ceramic substrate, an aluminum nitride ceramic substrate, and a silicon nitride ceramic substrate.

[0013] More optimally, in step 2, the grinding and cleaning process is specifically as follows: placing the laser punched ceramic substrate on a rubber pad, and polishing the substrate surface with 180-300 mesh and 600-800 mesh sandpaper in turn; then soaking the ceramic substrate in 60-80°C, 5%-10% volume fraction phosphoric acid for 10-15 minutes.

[0014] More optimally, in step 2, annealing treatment: annealing at 800-1100° C. for 6-12 hours in a nitrogen atmosphere.

[0015] More optimally, in step 2, the ultrasonic cleaning process is specifically as follows: ultrasonic alkali cleaning of the ceramic substrate, with an alkali cleaning mass concentration of 5-10% and a temperature of 50-60°C; then ultrasonic acid cleaning, with an acid cleaning mass concentration of 2-5% and a temperature of 30-40°C; then pure water ultrasonic cleaning, with a cleaning frequency of 20-40KHz; the conductivity of pure water is 1-10us / cm.

[0016] More optimally, in step three, the magnetron sputtering pretreatment step is: pretreat the titanium target / copper target, and burn the target surface by glow discharge, wherein the burning order is first glow burning the copper target, and then glow burning the titanium target, and the burning time is 600-900s; after the pretreatment, magnetron sputtering the titanium layer: in an argon atmosphere, first sputter a seed titanium layer of 40-60nm at a high pressure of 0.3-0.4Pa, and then sputter a compensation titanium layer of 60-90nm at a low pressure of 0.2-0.25Pa; the thickness of the magnetron sputtered titanium layer is 100-150nm.

[0017] More optimally, in step three, the magnetron sputtering copper layer: under argon atmosphere, double-target high and low double sputtering is adopted, the power of target A is set to 15-20KW, the power of target B is set to 5-13KW, the sputtering current is 10A-20A, and the sputtering voltage is 500-800V; first, the sputtering thickness is 1.6-1.8μm at a high pressure of 0.3-0.35Pa, and the sputtering temperature is 200-250℃; then, the sputtering thickness is 0.4-0.6μm at a low pressure of 0.2-0.25Pa, and the sputtering temperature is 150-200℃; the thickness of the magnetron sputtering copper layer is 2-2.4μm.

[0018] More optimally, in step 4, the electroplating process is: pickling → water washing → copper electroplating → water washing → drying.

[0019] More optimally, in step four, the electroplating copper thickening process adopts a high-copper and low-acid system; wherein copper sulfate pentahydrate is 200-260g / L; sulfuric acid is 40-90g / L; chloride ions are 40-70ppm; wetting agent is 10-15ml / L; copper plating brightener is 0.6-1.4ml / L; leveling agent is 25-35ml / L; temperature is 20-26°C, cathode current density is 1.5-2.5ASD, anode current density is 1-3ASD, and jet flow rate is 0.2-2.0L / Min / nozzle.

[0020] Beneficial effects of the present invention:

[0021] The present invention prepares a finished product by performing a punching process, a grinding and cleaning process, an annealing process, an ultrasonic cleaning process, a magnetron sputtering process, and an electroplating copper thickening process on a ceramic substrate. Compared with the previous DPC ceramic substrate manufacturing process, the present invention has a higher level of reliability and can reduce the poor bonding caused by raw material reasons, process reasons, etc. during the processing. Compared with the conventional DPC ceramic substrate manufacturing process, the ceramic sheet is subjected to surface treatments such as grinding and cleaning, sputtering process, and electroplating thickening after laser punching, which further improves the reliability and yield of the connection material of the power semiconductor device. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0023] Figure 1 It is a process flow chart of the present invention;

[0024] Figure 2 This is a microscopic state diagram of the hole after cleaning in step 2 of Example 1 of the present invention;

[0025] Figure 3is a schematic diagram of metallization after sputtering in step 3 of embodiment 1 of the present invention;

[0026] Figure 4 is a diagram showing the copper coverage in the hole of Example 1 of the present invention;

[0027] Figure 5 This is a thermal shock test diagram of Example 1 of the present invention;

[0028] Figure 6 This is a thermal shock test diagram of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Source of raw materials:

[0031] Aluminum nitride ceramic substrate, size specification is 76.2mm×76.2mm×0.3mm.

[0032] Example 1: Step 1: Punching: The aluminum nitride ceramic substrate is laser punched with a hole diameter of 70 μm, an instantaneous power of 1500 W, and an average power of 500 W;

[0033] Step 2: Grinding and cleaning: The aluminum nitride ceramic substrate is first subjected to plane grinding processing: the aluminum nitride ceramic substrate after laser punching is placed on a rubber pad, and the surface of the substrate is polished with 320-mesh and 600-mesh sandpapers in turn; the aluminum nitride ceramic substrate is then immersed in 75°C, 6% phosphoric acid for 11 minutes;

[0034] Annealing treatment: anneal the aluminum nitride ceramic substrate at 800°C for 6h in a nitrogen atmosphere;

[0035] Ultrasonic cleaning treatment: the ceramic substrate is subjected to ultrasonic alkali cleaning, the alkali cleaning mass concentration is 8%, and the temperature is 55°C; then ultrasonic acid cleaning is performed, the acid cleaning mass concentration is 4%, and the temperature is 35°C; then pure water ultrasonic cleaning is performed, and the cleaning frequency is 20KHz; the conductivity of pure water is 5us / cm; after the ultrasonic cleaning treatment is completed, it is baked at a high temperature of 120°C for 100min;

[0036] Step 3: magnetron sputtering treatment: The aluminum nitride ceramic substrate obtained in step 2 is first subjected to magnetron sputtering of a titanium layer: in an argon atmosphere, a seed titanium layer is first sputtered at a high pressure of 0.4 Pa to a thickness of 50 nm, and then a compensation titanium layer is sputtered at a low pressure of 0.2 Pa to a thickness of 70 nm; the magnetron sputtered titanium layer is 120 nm thick;

[0037] Then magnetron sputtering copper layer: in argon atmosphere, double-target high and low double sputtering is adopted, target A power is set to 17KW, target B power is set to 10KW, sputtering current is 15A, sputtering voltage is 600V; firstly, the sputtering thickness is 1.8μm at high pressure 0.3Pa, wherein the sputtering temperature is 220℃; then, the sputtering thickness is 0.6μm at low pressure 0.2Pa, wherein the sputtering temperature is 180℃; the thickness of magnetron sputtering copper layer is 2.4μm;

[0038] Step 4: Electroplating copper thickening treatment: The aluminum nitride ceramic substrate obtained in step 3 is electroplated with copper to prepare a finished product; the electroplating copper thickening process is direct current electroplating, and the system is a high-copper and low-acid system; wherein copper sulfate pentahydrate is 230g / L; sulfuric acid is 50g / L; chloride ions are 50ppm; wetting agent is 12ml / L; copper plating brightener is 1ml / L; leveling agent is 30ml / L; temperature is 23°C, cathode current density is 2ASD, anode current density is 2ASD, and jet flow rate is 1L / Min / nozzle.

[0039] Comparative Example 1: The grinding, cleaning and annealing steps in step 2 are removed, and the process parameters of the magnetron sputtering step in step 3 are modified. The rest is the same as in Example 1. The specific steps are as follows: Step 1: Punching: The aluminum nitride ceramic substrate is laser punched with a hole diameter of 70 μm, an instantaneous power of 1500 W, and an average power of 500 W;

[0040] Step 2: Ultrasonic cleaning: The ceramic substrate obtained in step 1 is subjected to ultrasonic alkali cleaning, with an alkali cleaning mass concentration of 8% and a temperature of 55°C; then ultrasonic acid cleaning, with an acid cleaning mass concentration of 4% and a temperature of 35°C; then pure water ultrasonic cleaning, with a cleaning frequency of 20KHz; the conductivity of pure water is 5us / cm; after the ultrasonic cleaning treatment is completed, it is baked at a high temperature of 100°C for 100min;

[0041] Step 3: magnetron sputtering treatment: magnetron sputter a 160nm titanium layer and then a 2.3μm copper layer on the aluminum nitride ceramic substrate obtained in step 2; the sputtering pressure is 0.3Pa, the sputtering temperature is 220°C, the sputtering current is 15A, the sputtering voltage is 600V, and the sputtering power is 15KW;

[0042] Step 4: Electroplating copper thickening treatment: The aluminum nitride ceramic substrate obtained in step 3 is electroplated with copper to prepare a finished product; the electroplating copper thickening process is direct current electroplating, and the system is a high-copper and low-acid system; wherein copper sulfate pentahydrate is 230g / L; sulfuric acid is 50g / L; chloride ions are 50ppm; wetting agent is 12ml / L; copper plating brightener is 1ml / L; leveling agent is 30ml / L; temperature is 23°C, cathode current density is 2ASD, anode current density is 2ASD, and jet flow rate is 1L / Min / nozzle.

[0043] Comparative Example 2: The annealing step in step 2 is removed, and the process parameters of the magnetron sputtering step in step 3 are modified. The rest is the same as Example 1. The specific steps are as follows: Step 1: Punching: The aluminum nitride ceramic substrate is laser punched with a hole diameter of 70 μm, an instantaneous power of 1500 W, and an average power of 500 W;

[0044] Step 2: Grinding and cleaning: The aluminum nitride ceramic substrate is first subjected to plane grinding processing: the aluminum nitride ceramic substrate after laser punching is placed on a rubber pad, and the surface of the substrate is polished with 320-mesh and 600-mesh sandpapers in turn; the aluminum nitride ceramic substrate is then immersed in 75°C, 6% phosphoric acid for 11 minutes;

[0045] Ultrasonic cleaning treatment: the ceramic substrate is subjected to ultrasonic alkali cleaning, the alkali cleaning mass concentration is 8%, and the temperature is 55°C; then ultrasonic acid cleaning is performed, the acid cleaning mass concentration is 4%, and the temperature is 35°C; then pure water ultrasonic cleaning is performed, and the cleaning frequency is 20KHz; the conductivity of pure water is 5us / cm; after the ultrasonic cleaning treatment is completed, it is baked at a high temperature of 120°C for 100min;

[0046] Step 3: magnetron sputtering treatment: magnetron sputter a 160nm titanium layer and then a 2.3μm copper layer on the aluminum nitride ceramic substrate obtained in step 2; the sputtering pressure is 0.2Pa, the sputtering temperature is 220°C, the sputtering current is 15A, the sputtering voltage is 600V, and the sputtering power is 15KW;

[0047] Step 4: Electroplating copper thickening treatment: The aluminum nitride ceramic substrate obtained in step 3 is electroplated with copper to prepare a finished product; the electroplating copper thickening process is direct current electroplating, and the system is a high-copper and low-acid system; wherein copper sulfate pentahydrate is 230g / L; sulfuric acid is 50g / L; chloride ions are 50ppm; wetting agent is 12ml / L; copper plating brightener is 1ml / L; leveling agent is 30ml / L; temperature is 23°C, cathode current density is 2ASD, anode current density is 2ASD, and jet flow rate is 1L / Min / nozzle.

[0048] Comparative Example 3: The process parameters of the magnetron sputtering treatment step in step 3 are modified, and the rest are the same as in Example 1, and the specific steps are as follows: Step 1: Punching treatment: The aluminum nitride ceramic substrate is laser punched with a hole diameter of 70 μm, an instantaneous power of 1500 W, and an average power of 500 W;

[0049] Step 2: Grinding and cleaning: The aluminum nitride ceramic substrate is first subjected to plane grinding processing: the aluminum nitride ceramic substrate after laser punching is placed on a rubber pad, and the surface of the substrate is polished with 320-mesh and 600-mesh sandpapers in turn, with a working current of 15A; then a cleaning agent is used for cleaning: the aluminum nitride ceramic substrate is soaked in 75°C, 6% phosphoric acid for 11 minutes, and then the surface is cleaned with a cleaning agent for 600 seconds; the main components of the cleaning agent include surfactants, defoamers, solubilizers, and detergents;

[0050] Annealing treatment: anneal the aluminum nitride ceramic substrate at 1000°C for 4 h in a nitrogen atmosphere;

[0051] Ultrasonic cleaning: The aluminum nitride ceramic substrate is ultrasonically cleaned; the ultrasonic cleaning includes ultrasonic alkaline acid cleaning in a thousand-level clearance environment and pure water ultrasonic cleaning in a hundred-level environment; the alkaline cleaning mass concentration is 8% and the temperature is 55°C; the acid cleaning mass concentration is 4% and the temperature is 35°C; the pure water ultrasonic cleaning frequency is 20KHz; the conductivity of pure water is 5us / cm; after the ultrasonic cleaning is completed, it is baked at a high temperature of 120°C for 100 minutes;

[0052] Step 3: magnetron sputtering treatment: magnetron sputter a 160nm titanium layer and then a 2.3μm copper layer on the aluminum nitride ceramic substrate obtained in step 2; the sputtering pressure is 0.2Pa, the sputtering temperature is 220°C, the sputtering current is 15A, the sputtering voltage is 600V, and the sputtering power is 15KW;

[0053] Step 4: Electroplating copper thickening treatment: The aluminum nitride ceramic substrate obtained in step 3 is electroplated with copper to prepare a finished product; the electroplating copper thickening process is direct current electroplating, and the system is a high-copper and low-acid system; wherein copper sulfate pentahydrate is 230g / L; sulfuric acid is 50g / L; chloride ions are 50ppm; wetting agent is 12ml / L; copper plating brightener is 1ml / L; leveling agent is 30ml / L; temperature is 23°C, cathode current density is 2ASD, anode current density is 2ASD, and jet flow rate is 1L / Min / nozzle.

[0054] Detection test:

[0055] Thermal shock test: The finished product prepared by the present invention is placed on a heating platform and maintained at 350°C for 5 minutes to observe whether it has blistering or other poor bonding phenomena. The results are shown in the following table:

[0056]

[0057] Conclusion: The present invention discloses a surface treatment process for a through-hole thin-film ceramic substrate. In this process, the surface of the ceramic substrate can be made smoother and cleaner by subjecting the punched ceramic substrate to grinding treatment + annealing + ultrasonic cleaning treatment, magnetron sputtering, and electroplating thickening processes, and the slag effect caused by laser punching can be reduced, thereby greatly improving the yield rate of the product. As shown in Example 1, after the finished product prepared by the present invention was subjected to a thermal shock test, there were no bubbles, the board surface was clean, no obvious plating rejection and particle residue were observed, and the bonding strength was OK. However, in the comparative examples where some steps were removed, the bonding strength was NG, which could not meet the requirements.

[0058] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0059] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A surface treatment process for a through-hole thin-film ceramic substrate, characterized in that: The following steps are involved: Step 1: Punch the ceramic substrate; Step 2: grinding and cleaning the surface of the ceramic substrate obtained in step 1, annealing, ultrasonic cleaning, and baking at 100-120° C. for 60 min-120 min; annealing: annealing at 800-1100° C. for 6-12 h in a nitrogen atmosphere; Step 3: magnetron sputtering is performed on the surface of the ceramic substrate obtained in step 2, and a titanium transition layer and a copper metal layer are sputtered respectively; magnetron sputtering titanium layer: in an argon atmosphere, firstly sputtering a seed titanium layer with a thickness of 40-60nm at a high pressure of 0.3-0.4Pa, and then sputtering a compensation titanium layer with a thickness of 60-90nm at a low pressure of 0.2-0.25Pa; the thickness of the magnetron sputtering titanium layer is 100-150nm; Step 4: The ceramic substrate obtained in step 3 is thickened by electroplating copper to obtain a finished product.

2. The surface treatment process of a through-hole thin-film ceramic substrate according to claim 1, characterized in that: In step 1, the ceramic substrate is punched by laser punching; during laser punching, the aperture is 70-100 μm, the instantaneous power is 1500-1800 W, and the average power is 500-700 W.

3. The surface treatment process of a through-hole thin-film ceramic substrate according to claim 1, characterized in that: In step 1, the ceramic substrate is one or more of an aluminum oxide ceramic substrate, an aluminum nitride ceramic substrate, and a silicon nitride ceramic substrate.

4. The surface treatment process of a through-hole thin-film ceramic substrate according to claim 1, characterized in that: In step 2, the grinding and cleaning process is specifically as follows: placing the laser punched ceramic substrate on a rubber pad, and polishing the substrate surface with 100-300 mesh and 600-800 mesh sandpaper in turn; then soaking the ceramic substrate in 60-80° C., 5%-10% volume fraction phosphoric acid for 10-15 minutes.

5. The surface treatment process of a through-hole thin-film ceramic substrate according to claim 1, characterized in that: In step 2, the ultrasonic cleaning process is specifically as follows: ultrasonic alkali cleaning of the ceramic substrate, with an alkali cleaning mass concentration of 5-10% and a temperature of 50-60°C; then ultrasonic acid cleaning, with an acid cleaning mass concentration of 2-5% and a temperature of 30-40°C; then pure water ultrasonic cleaning, with a cleaning frequency of 20-40KHz; the conductivity of pure water is 1-10us / cm.

6. The surface treatment process of a through-hole thin-film ceramic substrate according to claim 1, characterized in that: In step three, magnetron sputtering copper layer: in argon atmosphere, adopt double target high and low double sputtering, A target power is set to 15-20KW, B target power is set to 5-13KW, sputtering current is 10A-20A, sputtering voltage is 500-800V; first at high pressure 0.3-0.35Pa, sputtering thickness is 1.6-1.8μm, wherein the sputtering temperature is 200-250℃; then at low pressure 0.2-0.25Pa, sputtering thickness is 0.4-0.6μm, wherein the sputtering temperature is 150-200℃; the thickness of magnetron sputtering copper layer is 2.0-2.4μm.

7. The surface treatment process of a through-hole thin-film ceramic substrate according to claim 1, characterized in that: In step 4, the electroplating copper thickening process adopts a high-copper and low-acid system; wherein copper sulfate pentahydrate is 200-260g / L; sulfuric acid is 40-90g / L; chloride ions are 40-70ppm; wetting agent is 10-15ml / L; copper plating brightener is 0.6-1.4ml / L; leveling agent is 25-35ml / L; temperature is 20-26°C, cathode current density is 1.5-2.5ASD, anode current density is 1-3ASD, and jet flow rate is 0.2-2.0L / Min / nozzle.

Citation Information

Patent Citations

  • Surface treatment process of DPC ceramic substrate

    CN115394658A

  • Method for reducing cracks generated by punching of ceramic substrate

    CN116924828A

  • Pickling production line for surface treatment of ceramic substrate

    CN217774974U